Long-term decline of whitefish (Coregonus lavaretus) population in the boreal lake Pyhäjärvi, southwest Finland, relative to simultaneous abiotic and biotic changes - Sarvala, Jouko; Helminen, Harri; Karjalainen, Juha; Marjomäki, Timo J.; Forsman, Tero; Anttila, Lauri (EDP SCIENCES S A, 2025)
In recent decades many lake fish populations have faced complex pressures particularly due to climate warming and eutrophication. In Lake Pyhajarvi, southwest Finland, profound changes have occurred in the commercial winter fisheries targeting the coregonids vendace, Coregonus albula, and whitefish, Coregonus lavaretus. The responses of vendace have been examined earlier, and here the detailed analyses are extended to the whitefish. In the 1970s and 1980s, the coregonid fishery was sustainable, but in 1991-1998, intense exploitation led to recruitment overfishing of vendace. Despite temporarily improved growth and recruitment of whitefish during vendace decline, whitefish population biomass declined throughout the study period, while perch (Perca fluviatilis), roach (Rutilus rutilus) and ruffe (Gymnocephalus cernuus) increased and vendace and smelt (Osmerus eperlanus) maintained their abundance. As many other northern lakes, Pyhajarvi seems to be changing from coregonid to perch dominance due to climate warming and eutrophication. Whitefish decline was associated with decreases in fecundity, winter survival of embryos, and larval density. The spawning stock was kept small by intensive fishery. The decline of the relative fecundity was likely due to food competition with vendace and especially the perch and roach populations that increased with eutrophication and more frequent hot summers. The winter survival of whitefish embryos decreased when the introduced signal crayfish (Pacifastacus leniusculus) increased. Despite decreasing fishing effort in the 2000s the larval numbers continued to decline. In the prevailing circumstances in Pyhajarvi, whitefish will with high probability remain as a minor and still declining species of the fish assemblage.